PERLINDUNGAN HUKUM TERHADAP KONSUMEN DALAM TRANSAKSI ELEKTRONIK DI INDONESIA: TANTANGAN DALAM IMPLEMENTASI - Wulandari, Yudha Sri; Rismansyah (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2025)
Technological developments have encouraged the rapid growth of electronic transactions (e-commerce) in Indonesia. However, this convenience also raises vulnerabilities for consumers related to fraud, quality of goods, data confidentiality, and puts consumers in a weak bargaining position. This study aims to analyze the legal framework that protects e-commerce consumers in Indonesia, highlight implementation challenges, and identify effective solutions. This research uses normative legal research methods with legislative and conceptual approaches. The results show that primary legal protection is sourced from Law Number 8 of 1999 concerning Consumer Protection (UUPK) and Law Number 11 of 2008 concerning Information and Electronic Transactions (ITE Law), but there are still regulatory gaps and weaknesses in law enforcement. The main gap is the absence of substantial affirmation of civil liability for marketplace platforms that factually play an active role and make a profit. Conceptually, this condition demands the adoption of the doctrine of shared responsibility between the platform and the merchant. In addition, the dispute resolution mechanism through the Consumer Dispute Resolution Agency (BPSK) has proven to be ineffective due to execution constraints and spatial jurisdictional limitations. Therefore, regulatory harmonization is needed to explicitly define the Shared Liability platform, strengthen the government's institutional capacity for data security audits, and an urgent transition towards the implementation of the Online Dispute Resolution (ODR) system as a fast and efficient dispute resolution mechanism. These measures are crucial to achieve optimal protection and legal certainty in digital dynamics.